Optic nerve sheath diameter/eyeball transverse diameter ratio by ultrasound in prediction of increased intracranial pressure in children with viral encephalitis - Zhao, Chun; Sun, Peng-Cheng; Fang, Ke-Jie; Fu, Hui-Hui; Wei, Li-Feng; Miao, Yin-Yun; Guo, Xin-Xin; Weng, Xiao-Ling (Frontiers in Pediatrics, 2025)
IntroductionIncreased intracranial pressure (ICP) is common with viral encephalitis in children which is associated with complications and prognosis. The optic nerve sheath diameter (ONSD) is a new indicator for the assessment of intracranial pressure using ultrasound, CT scan and MRI imaging. Given the influence of physical development on ONSD size in children, we expect more accurate assessment of intracranial pressure with ONSD/ETD (eyeball transverse diameter) ratio by ultrasound. The aim of the study is to determine the performance of the ONSD/ETD ratio measurement to predict ICP occurring in children with viral encephalitis and evaluate the therapeutic effect.MethodsChildren with viral encephalitis from May 2022 to June 2024 were recruited in this study. The initial ONSD/ETD ratio measurement by ultrasound were completed before lumbar puncture. Children were divided into the increased ICP group and the normal ICP group based on whether the ICP was over 200 mmH2O measured by lumbar puncture. The ultrasound was repeated on the 3rd and 7th day of treatment.ResultsThe ONSD/ETD ratios measured in the two groups before treatment were 0.231 ± 0.019 and 0.182 ± 0.012, respectively (p < 0.01). The ONSD/ETD ratio on the 3rd day of treatment in the increased ICP group was significantly lower than the data before treatment (p < 0.01). The data on the 7th day of treatment in increased ICP group was significantly lower than the data before treatment (p < 0.01), but not statistically significant compared to the data on the 3rd day of treatment (p = 0.650). The ROC curve demonstrated an AUC for ONSD/ETD ratio in predicting the occurrence of increased ICP in children with viral encephalitis was 0.974 [95% confidence interval (CI): 0.939–1.000, p < 0.01], with a sensitivity of 95.1% and specificity of 93.3% at a cut-off value of 0.198.ConclusionOur study shows that ONSD/ETD can be used as an easy reference tool for evaluating ICP in children with viral encephalitis which can reflect the therapeutic effect.